Peculiarities of the state of peripheral oxygenation of tissues in different kinds of combined anesthesia in children with congenital surgical pathology - Vlasov, Aleksey (ScienceRise: Medical Science, 2021)
In the presented work, we have assessed the features of peripheral oxygenation in children with congenital malformations of the surgical profile under various types of combined anesthesia. The aim of the study. To assess the state of peripheral oxygenation in newborns and infants with congenital malformations with various types of anesthetic support. Materials and research methods. A retrospective study included 150 newborns and infants with congenital malformations of the surgical profile, depending on the anesthesia (inhalation + regional anesthesia; inhalation + intravenous anesthesia and total intravenous). The parameters of pulse oximetry were analyzed: peripheral oxygenation, heart rate. Additionally, the concentration of oxygen in the respiratory mixture of children was taken into account. Research results. Peripheral saturation did not critically decrease at all stages of observation, with the exception of a decrease in the indicator in children of group I compared with group III at the stage of induction into anesthesia (97.79±2.45 versus 98.79±1.63, at p˂0.05, respectively) and at the most painful moment of the operation (96.29±3.47 versus 98.10±2.47, with p˂0.05). At the painful moment of the operation, it was in children of group I that a drop in heart rate was noted compared to group III (127.98±13.77 and 136.10±15.37, respectively, with p˂0.05) and group II (134.02±18.43, at p>0.05) against the background of a decrease in SpO2. Newborns and group I infants required higher oxygen concentrations in the breathing mixture. A significant difference in the indicator is noted between groups I and III at the traumatic stage – 0.47±0.29 and 0.33±0.2, with p˂0.05, respectively, and immediately after the operation – 0.34±0,19 and 0.26±0.13, with p˂0.05, respectively. Conclusions. The expediency and effectiveness of pulse oximetry for children with congenital malformations at all stages of anesthetic support during surgical treatment was confirmed. The risk group for the formation of oxygen deficiency in organs and tissues, the occurrence of pain during the operation were newborns and infants, for whom combined anesthesia was chosen in the form of an inhalation method and regional anesthesia. In the case of the appointment of this type of anesthetic support, it is necessary to more closely monitor the indicators and promptly correct the deterioration of the child’s condition